State of the world's forests (SOFO) 1997 - FAO (FAO, 1997)
The book is divided into four main sections: a section on situation and prospects for forest conservation and development, which supplies information on forest cover, forest management and forest products; a section on policy, planning and institutional arrangements; a special issue section which presents information on efforts to develop criteria and indicators of sustainable forest management; and six regional reviews which together cover all the countries of the world